Case report: Ofatumumab treatment in anti-DPPX autoimmune encephalitis - Fu, Peicai; Hu, Zhenqiong; Zhang, Guopeng; Li, Zhijun (Frontiers in Immunology, 2024)
Dipeptidyl peptidase-like protein 6 (DPPX) antibody encephalitis is a rare autoimmune encephalitis. Diagnosis and treatment of DPPX remain challenging, particularly in patients with refractory disease. Herein, we report the first case of anti-DPPX encephalitis treated with ofatumumab. The patient had a chronic insidious onset and predominantly presented with severe neuropsychiatric symptoms and the typical triad of symptoms (weight loss, central nervous system hyperexcitability, and cognitive dysfunction). Positive anti-DPPX antibodies in the serum (1:1,000) and cerebrospinal fluid (CSF) (1:100) were detected at the disease peak. The patient was unresponsive to four types of standard immunotherapies (intravenous globulin, plasma exchange, steroids, and tacrolimus), resulting in a treatment switch to ofatumumab. After five doses of injection and 12 months of follow-up, the patient improved well, with only a mild cognitive deficit.